Flexible bifunctional catalytic electrode and preparation method thereof, and fiber zinc-air battery

CN121366899BActive Publication Date: 2026-10-16ZHEJIANG SCI-TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511345219.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-19
Publication Date
2026-10-16
Estimated Expiration
2045-09-19

AI Technical Summary

Technical Problem

然而,这些方法大多依赖于钴、镍等3d过渡金属,虽然它们有利于原位生长,但通常表现出有限的双功能活性(ΔE>0.65 V)

Benefits of technology

本发明的柔性双功能催化电极在碳纳米管薄膜上原位生长非晶态IrCoOx纳米叶片,通过引入铱元素形成双轨道桥,优化钴的3d轨道配置,并利用低温煅烧形成的无定形结构进一步提升了析氧反应(OER)与氧还原反应(ORR)的催化反应动力学,双功能电位差ΔE突破性地达到了0.55V;另外,电极具有优异的机械耐久性,在经历10000次弯曲循环后性能稳定;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121366899B_ABST
    Figure CN121366899B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of electrochemistry, and particularly relates to a flexible dual-function catalytic electrode, a preparation method thereof and a fiber zinc-air battery. The preparation method comprises the following steps: (1) soaking a carbon nanotube film in a Co-MOF precursor solution for several hours, then washing and drying to obtain Co-MOF / CNT; (2) immersing the Co-MOF / CNT in an iridium salt aqueous solution for several hours, then washing and drying to obtain IrCo-MOF / CNT; and (3) calcining the IrCo-MOF / CNT in an air atmosphere at a temperature increasing rate of 1-10 DEG C / min to 200-300 DEG C for 1-4 h to obtain the flexible dual-function catalytic electrode. The flexible dual-function catalytic electrode of the application in-situ grows amorphous IrCoO x nanosheet on the carbon nanotube film, forms a double-track bridge by introducing iridium elements, optimizes the 3d track configuration of cobalt, and further improves the catalytic reaction kinetics of the oxygen evolution reaction OER and the oxygen reduction reaction ORR by using the amorphous structure formed by low-temperature calcination, so that the dual-function potential difference DE is breakthroughly reached to 0.55 V.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical technology, specifically relating to a flexible bifunctional catalytic electrode and its preparation method, and a fiber zinc-air battery. Background Technology

[0002] Electronic textiles, as a potential platform for next-generation wearable technology, show broad application prospects in fields such as communications, healthcare, and sports. To ensure their continuous operation, developing flexible yet efficient compatible energy devices is particularly important. Among numerous candidate solutions, fiber zinc-air batteries (FZABs) stand out due to their high 1086 Wh·kg⁻¹ energy density. -1 FZABs have attracted widespread attention due to their theoretical energy density, good safety, and low cost. Their unique one-dimensional structure not only endows them with excellent mechanical flexibility but also enables seamless integration with electronic textiles. However, most reported FZABs still face problems of poor rate performance and low energy efficiency, mainly due to the slow kinetics of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) at their cathodes. Developing flexible bifunctional electrodes is crucial for achieving FZABs with fast-charging performance. These electrodes must not only possess excellent electrocatalytic activity to accelerate the slow ORR and OER processes but also exhibit outstanding mechanical robustness to cope with the challenges of repeated deformation in wearable applications.

[0003] Existing techniques typically involve loading powdered catalysts onto flexible substrates containing polymer binders. While such catalysts can achieve relatively high bifunctional electrocatalytic activity (ΔE = 0.60–0.65 V), the insulating properties of the binder hinder charge transport, thus reducing overall electrode performance. To overcome this issue, recent research strategies have increasingly shifted towards in-situ growth of catalysts on flexible substrates, thereby eliminating the need for binders and improving interfacial conductivity. However, these methods mostly rely on 3d transition metals such as cobalt and nickel, which, while beneficial for in-situ growth, generally exhibit limited bifunctional activity (ΔE > 0.65 V). Furthermore, systematic studies on the electrocatalytic stability of such bifunctional electrodes under dynamic deformation conditions are currently lacking, and their mechanical reliability in practical applications has not been fully verified. Summary of the Invention

[0004] Based on the aforementioned shortcomings and deficiencies in the prior art, one of the objectives of this invention is to at least solve one or more of the aforementioned problems in the prior art. In other words, one of the objectives of this invention is to provide a flexible bifunctional catalytic electrode and its preparation method, as well as a fiber zinc-air battery, that meet one or more of the aforementioned requirements.

[0005] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: A method for preparing a flexible bifunctional catalytic electrode includes the following steps: (1) The carbon nanotube film was immersed in the Co-MOF precursor solution for several hours, then rinsed and dried to obtain Co-MOF / CNT; (2) Immerse Co-MOF / CNT in an iridium salt aqueous solution for several hours, then rinse and dry to obtain IrCo-MOF / CNT; (3) IrCo-MOF / CNT is heated to 200-300℃ in air atmosphere at 1-10℃ / min and calcined for 1-4h to obtain a flexible bifunctional catalytic electrode.

[0006] As a preferred embodiment, in step (1), the carbon nanotube film is first soaked in nitric acid to remove impurities.

[0007] As a preferred embodiment, in step (1), the Co-MOF precursor solution includes a water-soluble cobalt salt, dimethylimidazole, and water.

[0008] As a preferred embodiment, the water-soluble cobalt salt is cobalt nitrate hexahydrate, cobalt chloride hexahydrate, or cobalt sulfate hexahydrate.

[0009] As a preferred embodiment, in step (1), the soaking time is 2 to 4 hours.

[0010] As a preferred embodiment, in step (2), the iridium salt in the iridium salt aqueous solution is sodium hexachloroiridate or iridium trichloride.

[0011] As a preferred embodiment, in step (2), the concentration of the iridium salt aqueous solution is 1 to 5 mM.

[0012] The present invention also provides a flexible bifunctional catalytic electrode prepared by the preparation method described in any of the preceding embodiments.

[0013] The present invention also provides a fiber zinc air battery, which uses the flexible bifunctional catalytic electrode as described above as the air cathode.

[0014] As a preferred option, fast charging performance testing is conducted within a current density range of 0.4–6 mA / g, and / or fast charging cycle performance testing is conducted under conditions of a charging current density of 0.4–6 mA / g and a discharging current density of 0.4 mA / g.

[0015] Compared with the prior art, the beneficial effects of this invention are: The flexible bifunctional catalytic electrode of the present invention enables in-situ growth of amorphous IrCoO on carbon nanotube films. xThe nanoblades, by introducing iridium to form a dual-orbital bridge, optimize the 3d orbital configuration of cobalt, and utilize the amorphous structure formed by low-temperature calcination to further enhance the catalytic reaction kinetics of oxygen evolution reaction (OER) and oxygen reduction reaction (ORR), achieving a breakthrough bifunctional potential difference ΔE of 0.55V; in addition, the electrode has excellent mechanical durability, and its performance remains stable after 10,000 bending cycles. The preparation method of the flexible bifunctional catalytic electrode of the present invention has the advantages of high reproducibility and simple synthesis process; The fiber zinc-air battery based on the flexible bifunctional catalytic electrode of this invention has excellent fast charging performance and ultra-long fast charging cycle life, enabling rapid energy replenishment and showing good application prospects in various demanding wearable application scenarios. Attached Figure Description

[0016] Figure 1 Morphological characterization of the flexible bifunctional catalytic electrode of Example 1 of the present invention: (a, b) are optical photographs of the flexible electrode, (c, d) are SEM images, and (e, g) are TEM images. Figure 2 The OER performance curves (a, d, g), ORR performance curves (b, e, h), and potential window curves (c, f, i) of the flexible bifunctional catalytic electrode of Example 1, the catalytic electrodes of Comparative Examples 1, 2, and 3, and the carbon nanotube film are shown. Figure 3 The bending stability test of the flexible bifunctional catalytic electrode of Example 1 of the present invention is as follows: (a, b) are the comparison of OER performance at different bending times during 10,000 bending cycles, (c, d) are the comparison of ORR performance at different bending times during 10,000 bending cycles, (e, f) are optical photographs before bending and after 10,000 bending cycles, and (g, h) are SEM photographs before bending and after 10,000 bending cycles. Figure 4 The fast charging performance (a), energy efficiency (b), and fast charging cycle performance (c) of the fiber zinc-air battery made from the flexible bifunctional catalytic electrode of Example 1 of the present invention are shown. Detailed Implementation

[0017] The following provides a detailed description of the flexible bifunctional catalytic electrode and its preparation method, as well as the fiber zinc-air battery of the present invention.

[0018] The flexible bifunctional catalytic electrode of the present invention is prepared by solvent method, metal ion doping loading, low temperature calcination and other processes, and can be directly used in electrochemical energy devices such as fiber zinc air batteries.

[0019] This invention involves in-situ growth of a Co-MOF framework on a carbon nanotube film and the introduction of iridium ions onto the surface of an organic framework precursor, enabling iridium ions to coordinate with functional groups in the precursor to form a metal-ligand composite structure. Subsequent low-temperature calcination yields a catalytic electrode with an amorphous structure. Furthermore, by controlling the details of the fabrication process, its performance can be further optimized. The resulting flexible bifunctional catalytic electrode can be directly used as a high-performance catalytic electrode material for fiber zinc-air batteries.

[0020] Specifically, the preparation method of the flexible bifunctional catalytic electrode of the present invention includes the following steps: (1) The carbon nanotube film was immersed in the Co-MOF precursor solution for 2-4 h, then rinsed and dried to obtain Co-MOF / CNT; The aforementioned carbon nanotube film was first soaked in 3M nitric acid to remove impurities; The aforementioned Co-MOF precursor solution includes a water-soluble cobalt salt, dimethylimidazole, and water; wherein the water-soluble cobalt salt is cobalt nitrate hexahydrate, cobalt chloride hexahydrate, or cobalt sulfate hexahydrate, which can be selected according to actual application requirements; (2) Immerse Co-MOF / CNT in an iridium salt aqueous solution for several hours, then rinse and dry to obtain IrCo-MOF / CNT; The iridium salt in the above-mentioned iridium salt aqueous solution is sodium hexachloroiridate or iridium trichloride, which can be selected according to the actual application requirements; The concentration of the above-mentioned iridium salt aqueous solution is 1-5 mM, which can be determined according to the actual application requirements; (3) IrCo-MOF / CNT is heated to 200-300℃ in air atmosphere at 1-10℃ / min and calcined for 1-4h to obtain a flexible bifunctional catalytic electrode.

[0021] The present invention also provides a flexible bifunctional catalytic electrode prepared by the above preparation method.

[0022] This invention also provides a fiber zinc air battery, which uses the above-mentioned flexible bifunctional catalytic electrode as an air cathode; For the fiber zinc-air battery, fast charging performance was tested in the current density range of 0.4–6 mA / g, and / or fast charging cycle performance was tested under the conditions of charging current density of 0.4–6 mA / g and discharging current density of 0.4 mA / g.

[0023] The following specific embodiments further explain and illustrate the flexible bifunctional catalytic electrode and its preparation method, as well as the fiber zinc-air battery of the present invention.

[0024] Example 1: The preparation method of the flexible bifunctional catalytic electrode in this embodiment includes the following steps: Carbon nanotube (CNT) films were immersed in 3M nitric acid for 3 hours to remove impurities and then dried in an oven at 60°C. Solution A was prepared by dissolving 0.582 g of cobalt nitrate hexahydrate in 40 mL of deionized water, and solution B was prepared by dissolving 1.314 g of dimethylimidazole in 40 mL of deionized water. These two solutions were mixed to obtain a Co-MOF precursor solution. The treated carbon nanotube films were completely immersed in the Co-MOF precursor solution and soaked at room temperature for 3 hours. The soaked samples were then thoroughly rinsed with deionized water and dried overnight in an oven at 60°C to obtain Co-MOF / CNTs. The prepared Co-MOF / CNT samples were then immersed in 4mM nitric acid solution. Iridium ions were infiltrated into the solution of Na₂IrCl₆·6H₂O for 3 hours. The solution was then thoroughly rinsed with deionized water to remove residual impurities, and dried at 60°C for 12 hours to obtain an IrCo-MOF / CNT intermediate. The dried intermediate was then calcined in air at a rate of 1°C / min to 200°C for 4 hours to obtain a flexible bifunctional catalytic electrode, namely IrCoO₂. x / CNT electrode.

[0025] The above IrCoO x The / CNT electrode was directly used as the air cathode in the zinc-air fiber battery. Fast charging performance was tested on the assembled zinc-air fiber battery within a current density range of 0.4–6 mA / g. Fast charging cycle performance was tested under charging current densities of 0.4–6 mA / g and discharging current densities of 0.4 mA / g.

[0026] like Figure 1 As shown, (a) is an optical photograph of the catalytic electrode placed on the flower stamen, demonstrating the thinness and lightness of the catalytic electrode; (b) shows that the catalytic electrode can be freely bent, exhibiting excellent mechanical flexibility; (c) and (d) show IrCoO x / CNTs grow uniformly on CNTs with a nano-leaf-like morphology; (e) shows an amorphous crystalline structure; (f) and (g) show a uniform distribution of Ir, Co, and O elements; The IrCoO in this embodiment x The OER overpotential of the / CNT catalytic electrode is 180 mV.

[0027] Example 2: The difference between the preparation method of the flexible bifunctional catalytic electrode in this embodiment and that in Example 1 is that the concentration of the Na2IrCl6·6H2O aqueous solution is adjusted to 2mM. The other steps are the same as in Example 1.

[0028] The IrCoO in this embodimentx The OER overpotential of the / CNT catalytic electrode is 254 mV.

[0029] Example 3: The preparation method of the flexible bifunctional catalytic electrode in this embodiment differs from that in Example 1 in that the immersion time of the Co-MOF / CNT sample in 4 mM Na2IrCl6·6H2O aqueous solution is adjusted to 1 h; The other steps are the same as in Example 1.

[0030] The IrCoO in this embodiment x The OER overpotential of the / CNT catalytic electrode is 270 mV.

[0031] Example 4: The difference between the preparation method of the flexible bifunctional catalytic electrode in this embodiment and that in Example 1 is that the dried intermediate is calcined at 200°C for 4 h in air at a heating rate of 10°C / min. The other steps are the same as in Example 1.

[0032] Comparative Example 1: The preparation method of the flexible bifunctional catalytic electrode in this comparative example differs from that in Example 1 in that: The Co-MOF / CNT sample was not immersed in Na2IrCl6·6H2O aqueous solution. Instead, it was heated to 200ºC in air at a heating rate of 1℃ / min and calcined for 4 hours to obtain the catalytic electrode CoO. x / CNT; The other steps are the same as in Example 1.

[0033] The catalytic electrode CoO in this comparative example x / CNT exhibits a distinct amorphous structure.

[0034] Comparative Example 2: The preparation method of the flexible bifunctional catalytic electrode in this comparative example differs from that in Example 1 in that: The dried intermediate was calcined at 400ºC for 4 h in air at a heating rate of 1ºC / min; The other steps are the same as in Example 1.

[0035] The catalytic electrode of this comparative example is C-IrCoO x / CNT exhibits a distinct crystalline structure.

[0036] Comparative Example 3: The preparation method of the flexible bifunctional catalytic electrode in this comparative example differs from that in Example 1 in that: The dried intermediate was calcined at 100ºC for 4 h in air at a heating rate of 1ºC / min; The other steps are the same as in Example 1.

[0037] The catalytic electrode IrCoO in this comparative example x / CNT-100 exhibits a distinct amorphous structure.

[0038] like Figure 2 As shown, IrCoO in Example 1 x / CNT at 10mA cm -2 At the given current density, the overpotential is only 180mV, the half-wave potential reaches 0.86V, and Δ E It has reached a breakthrough of 0.55V, while the CoO in Comparative Example 1... x / CNT, Comparative Example 2 C-IrCoO x / CNT, IrCoO3 (Comparative Example 3) x / CNT-100 and CNT's Δ E The values ​​are 0.79, 0.7, 0.76, and 0.96V.

[0039] like Figure 3 As shown, this indicates that the IrCoO in Example 1 x / CNT exhibits excellent OER flexural stability, ORR flexural stability, and mechanical stability.

[0040] like Figure 4 As shown, IrCoO in Example 1 x The fast-charging performance of fiber zinc-air batteries prepared using CNTs as air cathodes is shown in 6A g. -1 It still exhibits low charging voltage and high energy efficiency at low current density, demonstrating its excellent fast charging performance; at 6A g -1 At the charging current density, the battery cycled for more than 100 hours, demonstrating excellent fast charging stability.

[0041] In addition, the IrCoO from Example 1 will also be used. x The / CNT was compared with the catalytic electrodes published in existing papers, and the results are shown in Table 1.

[0042] Table 1 Performance Comparison of Catalytic Electrodes As shown in Table 1, regarding the choice of substrate, the catalytic electrode performance of both carbon cloth and carbon nanotube membranes used as substrates was in the range of 0.7-0.75, which is far lower than that of Ir-CoO in Example 1. x / CNT; Furthermore, the catalytic electrodes used for Ir and Co bonding are all powdered catalysts, whose performance is highly susceptible to the influence of binders and uneven growth. In summary, this invention is the first to apply a strategy combining amorphous and electronic control on Ir and Co to obtain Ir-CoO x / CNT, its catalytic performance Δ E It has achieved an unprecedented breakthrough.

[0043] Given that there are numerous embodiments of the present invention, and the raw materials and quantities involved can be selected within a limited range according to actual needs, and that the experimental data for each embodiment are extensive and numerous, it is not suitable to list and describe them one by one here. However, the content to be verified and the final conclusions obtained in each embodiment are similar. Therefore, the verification content of each embodiment will not be described one by one here.

[0044] The above description is merely a detailed explanation of preferred embodiments and principles of the present invention. For those skilled in the art, there may be changes in specific implementation methods based on the ideas provided by the present invention, and these changes should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a flexible bifunctional catalytic electrode, characterized in that, Includes the following steps: (1) The carbon nanotube film was immersed in the Co-MOF precursor solution for several hours, then rinsed and dried to obtain Co-MOF / CNT; (2) Immerse Co-MOF / CNT in an iridium salt aqueous solution for several hours, then rinse and dry to obtain IrCo-MOF / CNT; (3) IrCo-MOF / CNT is heated to 200-300℃ in air atmosphere at 1-10℃ / min and calcined for 1-4 h to obtain a flexible bifunctional catalytic electrode.

2. The preparation method according to claim 1, characterized in that, In step (1), the carbon nanotube film is first soaked in nitric acid to remove impurities.

3. The preparation method according to claim 1, characterized in that, In step (1), the Co-MOF precursor solution includes a water-soluble cobalt salt, dimethylimidazole, and water.

4. The preparation method according to claim 3, characterized in that, The water-soluble cobalt salt is cobalt nitrate hexahydrate, cobalt chloride hexahydrate, or cobalt sulfate hexahydrate.

5. The preparation method according to claim 1, characterized in that, In step (1), the soaking time is 2 to 4 hours.

6. The preparation method according to claim 1, characterized in that, In step (2), the iridium salt in the iridium salt aqueous solution is sodium hexachloroiridate or iridium trichloride.

7. The preparation method according to claim 1, characterized in that, In step (2), the concentration of the iridium salt aqueous solution is 1 to 5 mM.

8. A flexible bifunctional catalytic electrode prepared by the preparation method according to any one of claims 1-7.

9. A fiber zinc-air battery, characterized in that, The flexible bifunctional catalytic electrode as described in claim 8 is used as the air cathode.

10. The fiber zinc-air battery according to claim 9, characterized in that, Fast charging performance was tested in the current density range of 0.4–6 mA / g, and / or fast charging cycle performance was tested under the conditions of charging current density of 0.4–6 mA / g and discharging current density of 0.4 mA / g.

Citation Information

Patent Citations

  • Preparation of two-dimensional flaky cobalt-based bimetal organic framework material and application of two-dimensional flaky cobalt-based bimetal organic framework material in water electrolysis reaction

    CN114574893A

  • Carbon-based composite iridium-based electrocatalyst, preparation method thereof, electrode and zinc-air battery

    CN118538936A